ENGINEERING DOCUMENTATION OF ARCHAELOGICAL EXCAVATIONS OF THE SITE “EARLY (WOODEN) FORTIFICATION” IN THE INNER CITY OF PLISKA AS PART OF THE CULTURAL AND HISTORICAL HERITAGE OF THE REPUBLIC OF BULGARIA: ENGINEERING DOCUMENTATION OF ARCHAELOGICAL EXCAVATIONS OF THE SITE “EARLY (WOODEN) FORTIFICATION” IN THE INNER CITY OF PLISKA AS PART OF THE CULTURAL AND HISTORICAL HERITAGE OF THE REPUBLIC OF BULGARIA - Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The current paper presents briefly and in general terms the horizontal geodesic survey done by angle measurement, as well as the engineering documentation of the results of the stage from the archaeological excavations of the site “Early (wooden) fortification“ in the Inner city of Pliska in 2019.